Slovenski selitveni tokovi v Nemčijo in spreminjanje vloge slovenščine - Štumberger, Saška (Dve domovini, 2005)
Explained in the article are terms denoting Slovenians in German that are liked with the manner of crossing the border (legal - illegal), causes of migrations (economic - political), and with the duration for staying (temporary - permanent). The historical survey begins with the 19th century while the centre of the research is the time after World War II. The description of migration streams and life in Germany is based on articles published in Slovenian magazines and newspapers and on interviews with Sloveni and in Germany. Particularly precisely described are events, researches and articles in the media that have influenced in Slovenia (Yugoslavia) and in Germany on the changing of the role of Slovenian language and attitude towards bilingualism.
Keywords: bilingualism; dvojezičnost; Germany; Nemčija; Slovene; slovenski izseljenci; slovenščina